Predictors of Success in Advance Higher Education: A Case in Northwest Samar State University, Philippines - Donald M. Patimo; Ma. Bernadette A. Lucero (Research in Social Sciences and Technology, 2021)
Teachers play a significant role in the preparation of our youth as they make important decisions about education, work, and life. Existing studies on the correlations between teaching proficiency and academic performance of the students are primarily limited to elementary, secondary, and tertiary levels. Considering the big difference between advance higher education and other educational levels, there is a need to explore the relationship of the teaching proficiency to the academic performance of the students in advance higher education. This study made use of the descriptive-correlation research design. Survey questionnaires were distributed to all advance higher education faculty members and students from School Years 2015 to 2017 at Northwest Samar State University. Statistical tools like frequency and percentage distribution, means, standard deviations, and regression analysis were used for the analysis of the data. Results showed that most of the advance higher education faculty members are male, married, doctorate holders, professionals, research-oriented, very satisfactory performers, and possess good financial status. The best predictor of the academic performance of the advance higher education students is the work experience of the faculty members.